A riboflavin transporter deficiency presenting as pure red cell aplasia: a pediatric case report - Cheng, Jingying; Yao, Jiafeng; Zhao, Shasha; Fu, Lingling; Zhang, Liqiang; Jiang, Jin (Frontiers in Pediatrics, 2024)
Introduction: Riboflavin transporter deficiency (RTD) is a rare genetic disorder that affects riboflavin transport, leading to impaired red blood cell production and resulting in pure red cell aplasia. Recognizing and understanding its clinical manifestations, diagnosis, and management is important.Case presentation: A 2-year-old patient presented with pure red cell aplasia as the primary symptom of RTD. After confirming the diagnosis, rapid reversal of anemia was achieved after high-dose riboflavin treatment. Conclusion: RTD often has an insidious onset, and neurological symptoms appear gradually as the disease progresses, making it prone to misdiagnosis. Genetic testing and bone marrow biopsy can confirm the diagnosis.